RESPONSE OF INTEGRATED NUTRIENT SUPPLY ON YIELD OF WHEAT AND PHYSICAL-CHEMICAL PROPERTIES OF SOIL - TARIKA SHARMA (The Bioscan, 2015)
The treatment with application of 50% NPK + 50% FYM (T6) registered higher crop yield (32.61 q ha-1) relative to control (T1). The soil parameters; organic carbon content (0.87%), cation exchange capacity (13.80 Cmolkg-1) and available Nitrogen (746.4 kg ha-1) and Phosphorus (48.3 kg ha-1) were statistically different from that of control (T1). The findings of the trial suggested that crop yield and soil properties may be improved significantly by application of organic with inorganic for longer time. Hence, instead of using chemical fertilizer alone, the integrated use could be more effective and sustainable for environment and agriculture.